Pengendalian Bahan Baku menggunakan Metode Min-Max Stock pada Kopi Badjoeri - Arif Kurniawan Putra; Nita P. A. Hidayat; Reni Amaranti (UNISBA Press, 2024)
Abstract. Kopi Badjoeri, a company in the food and beverage industry, manufactures processed products from coffee. The strategic approach employed is Make to Order (MTO). Analysis of the frequency of raw material shortages from January to October 2022 indicates that Kopi Badjoeri frequently experiences shortages with fluctuating occurrences each month. This condition arises due to insufficient planning in raw material procurement, often occurring abruptly, while the lead time for raw material procurement is relatively long. Shortages of raw materials often result in lost sales as consumers switch to other products or cancel their orders. This situation underscores the need for more effective inventory management. The aim of this research is to categorize raw materials according to their classifications, establish policies for raw material inventory, determine minimum and maximum inventory levels, measure inventory turnover to understand raw material rotation, and develop appropriate inventory control methods. The approaches used include the ABC-FSN-VED classification method and min-max stock. The research findings indicate that the inventory management method most suitable for the characteristics of raw materials and the Kopi Badjoeri company is the min-max stock method. Recommendations for improvement include determining end-of-stock value, safety stock, maximum and minimum inventory levels, reorder point, order quantity, and the frequency of raw material ordering to address issues of shortages and excess stock, thus ensuring more efficient fulfillment of consumer needs. Abstrak. Kopi Badjoeri, sebuah perusahaan di bidang makanan dan minuman, meproduksi produk olahan dari kopi. Pendekatan strategis yang diterapkan adalah Make to Order (MTO). Analisis frekuensi kehabisan bahan baku dari Januari hingga Oktober 2022 menunjukkan bahwa Kopi Badjoeri sering mengalami kekurangan bahan baku dengan tingkat kejadian yang berfluktuasi tiap bulan. Kondisi ini disebabkan oleh kurangnya perencanaan dalam pengadaan bahan baku, yang seringkali terjadi mendadak, sementara waktu tunggu untuk pengadaan bahan baku relatif lama. Kekurangan bahan baku sering kali mengakibatkan hilangnya penjualan karena konsumen beralih ke produk lain atau membatalkan pesanan mereka. Kondisi ini menandakan kebutuhan akan manajemen persediaan yang lebih efektif. Penelitian ini bertujuan untuk mengelompokkan bahan baku sesuai dengan klasifikasinya, menetapkan kebijakan persediaan bahan baku, menentukan tingkat minimum dan maksimum persediaan, mengukur inventory turnover untuk mengetahui rotasi bahan baku, dan mengembangkan metode pengendalian persediaan yang sesuai. Pendekatan yang digunakan meliputi metode klasifikasi ABC-FSN-VED dan min-max stock. Hasil penelitian menunjukkan bahwa manajemen persediaan yang paling sesuai dengan karakteristik bahan baku dan perusahaan Kopi Badjoeri adalah metode min-max stock. Rekomendasi perbaikan termasuk penentuan nilai stok akhir, safety stock, persediaan maksimum dan minimum, reorder point, order quantity, serta frekuensi pemesanan bahan baku untuk mengatasi masalah kekurangan dan kelebihan stok, sehingga kebutuhan konsumen dapat terpenuhi dengan lebih efisien.